(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The properties of both inorganic and organic powder ingredients play a certain role in the preparation of chemical preparations based on them. Therefore, first of all, before obtaining high-quality chemical preparations, it was necessary to study the properties of powder ingredients. Note that for the preparation of high-quality chemical reagents, bulk density, specific gravity, density and granulometric composition of powder ingredients play a special role.